2013
DOI: 10.1186/1471-2148-13-234
|View full text |Cite
|
Sign up to set email alerts
|

Growth reaction norms of domesticated, wild and hybrid Atlantic salmon families in response to differing social and physical environments

Abstract: BackgroundDirectional selection for growth has resulted in the 9-10th generation of domesticated Atlantic salmon Salmo salar L. outgrowing wild salmon by a ratio of approximately 3:1 when reared under standard hatchery conditions. In the wild however, growth of domesticated and wild salmon is more similar, and seems to differ at the most by a ratio of 1.25:1. Comparative studies of quantitative traits in farmed and wild salmon are often performed by the use of common-garden experiments where salmon of all orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(124 citation statements)
references
References 98 publications
(140 reference statements)
9
113
2
Order By: Relevance
“…In general, we found that V A (and hence evolvability) was lower in the FF group compared with the WW group, which is in line with previous findings that genetic variation in farm salmon strains are often lower than in wild strains (Norris et al, 1999;Skaala et al, 2004). Interestingly, Solberg et al (2013b) reported reduced heritability of juvenile mass in farm-provenance Atlantic salmon, compared with progeny of wild parents, when both were reared under standard hatchery conditions with unrestricted access to food. This pattern was reversed, however, when access to food was restricted, possibly reflecting selective mortality against the slowest-growing wild genotypes (Solberg et al, 2013b).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In general, we found that V A (and hence evolvability) was lower in the FF group compared with the WW group, which is in line with previous findings that genetic variation in farm salmon strains are often lower than in wild strains (Norris et al, 1999;Skaala et al, 2004). Interestingly, Solberg et al (2013b) reported reduced heritability of juvenile mass in farm-provenance Atlantic salmon, compared with progeny of wild parents, when both were reared under standard hatchery conditions with unrestricted access to food. This pattern was reversed, however, when access to food was restricted, possibly reflecting selective mortality against the slowest-growing wild genotypes (Solberg et al, 2013b).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, Solberg et al (2013b) reported reduced heritability of juvenile mass in farm-provenance Atlantic salmon, compared with progeny of wild parents, when both were reared under standard hatchery conditions with unrestricted access to food. This pattern was reversed, however, when access to food was restricted, possibly reflecting selective mortality against the slowest-growing wild genotypes (Solberg et al, 2013b). We also found strong positive genetic correlations between L F and mass (40.85 in all samples), which is higher than the median r G of +0.71 reported by Carlson and Seamons (2008) for pairs of morphological traits.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study performed under hatchery and semi-natural conditions, we demonstrated that the relative differences in growth between wild and farmed juvenile salmon decreased along an environmental gradient approaching more natural conditions (Solberg et al, 2013b). However, the most natural conditions included in that study, which was conducted in the period between egg hatching and the fry stage, only included a semi-natural habitat with hiding places and competition for food.…”
Section: Introductionmentioning
confidence: 68%
“…The relative difference in weight between farmed and wild salmon at the fresh water stage has been documented to be small in the wild, e.g., in River Guddal offspring of farmed salmon outgrew offspring of wild salmon at a maximum of 1.25:1 at the smolt stage . Furthermore, we have previously demonstrated that the relative difference in weight between farmed and wild salmon decreased when competition and mortality levels increased along an environmental gradient approaching natural conditions (Solberg et al, 2013b). Our previous study, based upon the same genetic material as included in this study, were performed along an environmental gradient without predation.…”
Section: Discussionmentioning
confidence: 95%
“…Because of genetic selection, the mean mass of AquaGen salmon in fish farms has increased several fold compared with similar-aged, wild conspecifics (Gjedrem 2010, Solberg et al 2013). Increased growth is also observed when farmed salmon are released into the wild (Fleming et al 2002, McGinnity et al 2003.…”
Section: Discussionmentioning
confidence: 99%